The mystery of mucormycosis in COVID-19: A multifactorial menace or an enigmatic delta variant associated phenomenon? An exploratory study from a tertiary care centre in North India with a brief literature review - Deepjyoti Kalita; Mohit Bhatia; Udayakumar Sasi Rekha; Arpana Singh (Wolters Kluwer Medknow Publications, 2022)
Background: There was a global surge in cases of mucormycosis in COVID-19 patients during the second wave of the pandemic in 2021, reported especially from India. Various predisposing factors such as diabetes mellitus, rampant use of corticosteroids, and COVID-19 per se may be responsible for this spike. Some public health experts have postulated that the epidemiological link between the Delta variant of SARS-CoV-2 and mucormycosis should be explored. Material and Methods: A retrospective exploratory study was conducted, in which data of 15 laboratory-confirmed cases of COVID-19 with mucormycosis and/or aspergillosis co-infections were collected after obtaining approval from the institute's ethics committee. These patients were admitted to the Mucor wards of our hospital. The positive COVID-19 status of these patients was confirmed by reverse transcriptase-polymerase chain reaction (RT-PCR). The residual SARS-CoV-2 RNA containing elutes of these patients were stored at −80°C in deep freezers and subjected to whole-genome sequencing in June 2021 at the National Centre for Disease Control (NCDC), New Delhi, India as part of the Indian SARS-CoV-2 Genomic Consortia (INSACOG) program. Concomitant fungal infections in these patients were diagnosed by KOH wet mount and fungal culture as per standard guidelines. Descriptive statistics in the form of percentages and median were used to report the findings. Results: Periorbital swelling and ocular pain (14/15; 93.33%), followed by facial swelling (11/15; 73.33%) and nasal obstruction (9/15; 60%), were the most common clinical features observed in these patients. Rhizopus arrhizus was the most common causative fungal agent (12/15; 80%). The majority of the patients (9/13; 69.23%) were infected with the Delta variant of SARS-CoV-2. Conclusion: COVID-associated mucormycosis seems to be multifactorial in origin. Although there may be a possible association between mucormycosis and the Delta variant, more studies should be conducted to explore this seemingly reasonable proposition.